Political ‘Harlotry’: Interrogating the Implications of Party Defection in Consolidating Democracy in Nigeria - Aliegba, Becky A.; Agaigbe, Faeren M. (NIU Journal of Social Sciences; Vol 7 No 3 (2021): KIU Journal of Social Sciences, Vol. 7 No. 3, September 2021, 2021)
Nigeria’s democracy, especially in the fourth Republic has been characterized by party defections and decamping of political gladiators to other parties. It has become a seasonal fad that peaks at election period. It is a habitual search for the ‘right clime’ to realize their dreams and ambitions. This paper examines the implications of this, on the sustainability of democracy in Nigeria. The elite theory is engaged in this discourse, while both primary and secondary sources of data are used. The study demonstrates that while party defections are an integral part of democratic processes, lack of party ideologies and internal party democracy, are the major factors responsible for the prevailing scenario in Nigeria’s political system. The paper also observes that, since party defections are not driven by fundamental ideological considerations, the outcome is an unstable opposition which is unable to sustain and consolidate the gains of democracy. The paper recommends that party manifestoes be supreme with laws made to limit defections. Elected representatives should also lose their seats if they defect outside the procedure to be provided for in the electoral act . Keywords: Defection, Democracy, Consolidation, Party